Estudio del comportamiento de los precios por calidad de leche que perciben los pequeños productores asociados del sector norte del cantón Cayambe periodo 2004-2013 - Estrada Monteros, Juan Carlos (2015)
The progressive growth of the livestock sector is an economic and social reality in our country, but needs to improve the product in this market have not been fully met. Because this situation arises this project, in order to establish the behavior of prices received by dairy farmers in a collection center where the main focus is product quality, added value and consumer acceptance. As target market study have been considered collection centers dairy farmers in the northern sector of Canton Cayambe, due to its agricultural guidance and advanced development and growth experienced in recent years. A study of the major variables that define quality in milk offered by each of the producers and the impact it has on determining the final price will be made. The needs of consumers and producers, based on the quality of the product to determine the impact that has this factor in determining the offer price and sale to the final consumer over a defined period of time (Since 2008 to 2013). Comparative analysis of agricultural production Canton regarding dairy products will be made, thus verifying its development, profitability and sustainability over time; also considered as an important factor increasing or reducing production cost and the selling price for the consumers.